Biological and economic vulnerabilities of fixed TACs in small pelagics: An analysis of the European anchovy (Engraulis encrasicolus) in the Gulf ofCádiz. (April 2017) - Ruiz, Javier; Rincón, Margarita María; Castilla, David; Ramos, Fernando; del Hoyo, Juan José García
Abstract: A coupled population dynamics and economic model is applied to the purse seine anchovy-fishery in the Gulf of Cádiz. The model simulates the population dynamics, landings and profits on a probabilistic frame. These simulations are used to assess the biological and economic consequences of an individual quota management framework enveloped by a fixed Total Allowable Catch (TAC), the present strategy used to manage this stock in the Spanish fishery. Our results accurately indicate that this strategy magnifies the biological and economic vulnerabilities associated with the exploitation of the stock, thus jeopardizing the sustainability of this fishery. Alternative strategies, such as an adaptive TAC, are explored. The results indicate that even a basic implementation of an adaptive TAC seems more favorable than the present strategy in the necessary equilibrium between profits and sustainability. This paper provides tools and an assessment that may also be useful for other small pelagic fisheries.